Patients’ experiences of adverse symptoms, emotions, and coping strategies in connection to treatment of head and neck cancer - an interview study - Ellie Saghafi; Charlotte Andrén Andås; Jenny Bernson; Göran Kjeller (BMC Oral Health, 2023)
Abstract Purpose This study aimed to increase the understanding of emotions and coping strategies used by head and neck cancer patients before cancer treatment, and to explore their emotions and coping strategies in relation to symptoms and side effects after treatment. Furthermore, we aimed to investigate the patients’ perceptions of received treatment and support. Methods Semi-structured in-depth interviews were conducted with 10 patients who had been treated for head and neck cancer, which included radiotherapy, at the Department of Oncology and the Department of Oral and Maxillofacial Surgery at Sahlgrenska University Hospital in Gothenburg. The interviews were analyzed in accordance with the method for Qualitative Content Analysis. Results The result picture revealed three head themes. The first theme “Management of simultaneously influencing mind-sets before cancer treatment” described the patients experiences of feeling “Scared and worried,” “Lonely and disappointed,” and “Relieved and confident”, and how they tried to handle the diagnosis and preparations for treatment by “Applying a positive mind-set”, “Searching for support,” and “Trusting the healthcare system”. The second theme “Experiences of becoming a pale shadow of oneself”, illustrated experiences of affecting post-treatment symptoms and side effects. To which, the last theme “Handling contextual influencing experiences after cancer treatment” displayed post-treatment emotions of being “Shocked and disappointed” and “Concerned and unsupported” but also “Grateful and forward-thinking”, where strategies such as “Appreciating Life”, “Networking socially,” and “Adapting to the new life” were used. Conclusions The results indicated the need for a more patient-centered care approach, with clearer structures and improved individual support both before and after treatment and in connection to rehabilitation. Patients’ cognitive changes after cancer treatment should be considered in the aftercare, which should also include adaptation to situation and strengthening of patients’ self-management as a goal.